2012
DOI: 10.1177/0022034511435260
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinduction

Abstract: Since the discovery of osteoinduction in the early 20th century, innovative biomaterials with osteoinductive potential have emerged. Over the last 50 years, however, our ability to describe biological phenomena accurately has been improved dramatically by advancements in cell and molecular biology. The aim of this review is to divide the osteoinduction phenomenon into 3 principles: (1) mesenchymal cell recruitment, (2) mesenchymal differentiation to bone-forming osteoblasts, and (3) ectopic bone formation in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
136
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(153 citation statements)
references
References 82 publications
(85 reference statements)
3
136
0
2
Order By: Relevance
“…On the other hand, it is stated that mineralized bone allografts have the advantage of providing both the BMP and the minerals necessary to achieve osteoinductive properties and presence of both BMPs and osteoinductive minerals can be the main advantage of FDBAs (Minichetti et al 2004). Although some previous clinical studies reported superior osteoinductive potential of human demineralized bone allografts compared to mineralized types (Piatelli et al 1996;Miron and Zhang 2012;Urist and Strates 2009;Wood and Mealey 2012), to the best of our knowledge, no detailed comparative in vitro study is available in this regard. For example, there is a comparative in vitro study on the effect of soluble materials released from allografts only on proliferation and alkaline phosphatase activity of mouse myoblast C2C12 cell line (Bormann et al 2010).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…On the other hand, it is stated that mineralized bone allografts have the advantage of providing both the BMP and the minerals necessary to achieve osteoinductive properties and presence of both BMPs and osteoinductive minerals can be the main advantage of FDBAs (Minichetti et al 2004). Although some previous clinical studies reported superior osteoinductive potential of human demineralized bone allografts compared to mineralized types (Piatelli et al 1996;Miron and Zhang 2012;Urist and Strates 2009;Wood and Mealey 2012), to the best of our knowledge, no detailed comparative in vitro study is available in this regard. For example, there is a comparative in vitro study on the effect of soluble materials released from allografts only on proliferation and alkaline phosphatase activity of mouse myoblast C2C12 cell line (Bormann et al 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Also, once the matrix mineralization is completed, extracellular calcium deposition Fig. 4 The effect of 20 and 40 mg of partially demineralized (A and B test groups), fully demineralized (C-G test groups) and mineralized (H and I test groups) freeze-dried bone allografts (per well/2 mL culture medium) on bone mineralization in MG-63 cells at 72 h after treatment (non-clear nodules in G group and the osteogenic medium group are marked with arrows) Cell Tissue Bank (indicator of bone formation) can be visualized (Boufker et al 2010;Roberts et al 2011;Miron and Zhang 2012;Beederman et al 2013). Cytotoxicity evaluation is very important for preliminary analysis of biomaterials (such as allografts) and cytotoxicity must be evaluated prior to assessment of cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be easily molded into the bone defect within a short setting time. It should be osteoconductive, osteoinductive [11] and resorbable. It should be possibly traceable in vivo; to this aim radiolucency is ideal to allow optimal radiographic assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The use of stem cells to repair organs and injured tissues opens new avenues to a new era of possibilities inside the medical/dental fields, referred to as regenerative medicine [13]. Over the last few years, regenerative medicine has brought a revolutionary potential comparable to historic discoveries, as was the case with penicillin.…”
Section: Introductionmentioning
confidence: 99%